Kushite Stamp Impressions from Selib 2, Sudan - Hajduga, Roksana (Études et Travaux, 2021)
More than two hundred sealings have been found since 2010 at Selib 2, a small Meroitic settlement in the Dongola Reach. This group come from the same context, in the S2/1/2010 storehouse and the most prominent building within the settlement. This paper focuses on selected impressions of thirty-one seals found on sealings and discusses them mainly in terms of iconography. Motifs from the sealings are both figural and non-figural. They reflect Meroitic beliefs, culture and politics. The catalogue and description of individual sealings, complete with photographs and drawings of stamp impressions, provide a firm base for preliminary observation regarding religion, symbols used by administrations and political propaganda, as well as allowing one to trace external influences and adaptation of foreign patterns.